Kidney transplantation using complement inhibitor in a patient suffering from atypical hemolytic-uremic syndrome associated with factor H antibodies: successful prevention of recurrence of the underlying disease - E. I. Prokopenko; S. A. Pasov; A. V. Vatazin; A. Ya. Tsalman; T. E. Pankratenko; G. A. Generalova (Вестник трансплантологии и искусственных органов, 2020)
Atypical hemolytic-uremic syndrome (aHUS) is an extremely rare complement-mediated disease that belongs to the group of thrombotic microangiopathies (TMA). It often reoccurs after kidney transplantation (KT). Previously, KT was considered contraindicated in both children and adults with aHUS due to high (up to 50% and above) incidence of early graft loss associated with post-transplant recurrent TMA. Introduction of specific complement inhibitor therapy into clinical practice has improved outcomes in patients with aHUS and has significantly reduced the risk of post-transplant recurrence of underlying disease. We describe the clinical observation of a 20-year-old female patient with aHUS associated with antibodies to factor H, a major regulator of complement activation. The patient underwent KT and eculizumab was used for prophylactic purposes. In the postoperative period, the patient developed ureteral necrosis that required reconstructive surgery, followed by graft pyelonephritis. Despite postoperative complications, which were highly likely to trigger uncontrolled complement activation, TMA recurrence was avoided due to early treatment of the complications and prophylactic use of complement inhibitor therapy.